Attitudes of Young People Towards Lakes as a Premise for Their Public Participation in Environmental Management - Cichoń, Małgorzata; Warachowska, Weronika; Łowicki, Damian (Frontiers in Environmental Science, 2021)
Lake protection is a very important element of environmental management. This is especially true of lake districts, where the lakes are an important resting place for residents, especially young people. The crucial is the question whether young people who participate in lake management in the future, are ready for it. It was assumed that their attitude towards lakes would be an indicator of such preparation. This study aimed to define a set of respondents' features that may condition the specific model of participation. Based on the research conducted among young residents (N=167) of the Szczecinecki District in Poland, it was found that their pro-environmental attitudes were dominated by high values of the traits that make up the emotional component, average values of the cognitive component and the lowest values of activity. The lower the score of the overall attitude, the more often the respondents chose Recreational Lakes, rather than General Development or Natural Lakes. The most important feature that may determine the level of participation in the future is readiness to act. A comprehensive attitude index was created, which shows that it is worth examining the characteristics of respondents that correlate with the willingness to act, i.e. knowledge, logical thinking, creativity and belief in the effectiveness of actions taken and attachment to the place of residence, when planning participatory management in lakeland areas.